EDUKASI PEMILAHAN SAMPAH SEBAGAI UPAYA PENINGKATAN KESADARAN LINGKUNGAN MASYARAKAT DI BANJAR SENGGUAN, DESA SINGAPADU - Muhammad Zainudin Firmansyah; Afrilus Baptisa; I Kadek Dwi Jaya Antara; Maya Patricia; I Made Ari Suka Arsa; I Komang Aldita Maha Putra; Ni Komang Sukani Darmawati; Kadek Mas Sutatenaya (Widyadari, 2026)
Community Service Program (KKN) is one form of implementation of the Tri Dharma of Higher Education, focusing on community service through the direct application of knowledge. This activity aims to bridge academic concepts with real-world needs in the community. This article analyzes the implementation of the Thematic KKN program, which focused on waste sorting education in Banjar Sengguan, Singapadu Village, Sukawati District, Gianyar Regency. The main problems faced by the community were low awareness of separating organic, inorganic, and residual waste, as well as limited educational resources to support waste management. The method used was a participatory and educational approach through observation, outreach, direct education, and the provision of supporting media such as separate trash bins and information boards. The results of the activity showed an increase in community knowledge and awareness of waste management, demonstrated by the adoption of waste sorting habits at the household level. This program also had a positive impact on the PKK (Family Welfare Movement) women's group, Sekaa Teruna Teruni (Teruna Teruni Youth Group), elementary school students, and early childhood education in developing clean and healthy lifestyles. Thus, this KKN program contributes to creating a cleaner, healthier, and more sustainable environment based on community participation.